The emergence of personhood – why the evolution of the moral sense and symbolic behaviour defines the human self - van Huyssteen, Wentzel (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
In this essay I want to ask whether contemporary theories of human evolution might provide us with important bridge theories to theological anthropology and thus to a positive and constructive way of appropriating Darwinian thought for Christian theology. From a more philosophical point of view I am asking whether Darwin’s perspective on human evolution can help us move forward to more constructive, holistic notions of self and personhood. In John de Gruchy’s remarkable new book, Led into Mystery, we not only see this kind of “archaeology of personhood” strongly implied, but de Gruchy lifts up issues that are of great importance for evolutionary anthropology, and goes into a direct dialogue with neuropsychology and the neurosciences. In so doing he reveals the crucial impact of these sciences for central theological themes like the question of God, the perennial theodicee problem, the imago Dei, human consciousness, free will, life after death, and brain, mind, body and soul. In this way De Gruchy touches directly on some of the greatest controversies in current science and theology discussions. I would like to show that John de Gruchy places these crucial interdisciplinary issues in the centre of discussions on the human self, and in so doing opens up exciting trajectories that even go beyond the focused scope of his own project – notably challenging implications for the evolution of morality and of religion.